A 14-year-old girl with tuberculous otitis media and brain abscess - Peninnah Oberdorfer (2018)
Tuberculosis is a rare cause of chronic suppurative otitis media and mastoiditis. Intracranial complications are rare. The authors report a case of a 14-year-old girl with chronic otitis media of her right ear for 2 years. Her presentation was as follows: 10 days before admission she had a high fever, headache, alteration of consciousness and a generalised seizure. CT scanning of her brain showed right otomastoiditis with early brain abscess of the right cerebellum. She underwent right radical mastoidectomy and aspiration of the cerebellar abscess. The pus from the mastoid and cerebellar abscess was stained positive for acid-fast bacilli (AFB). The pus culture grew Mycobacterium tuberculosis (MTB). Her discharge diagnosis was tuberculous mastoiditis (TM) with cerebellar abscess. Long-term treatment plans included antituberculous drugs for 1 year. Copyright 2012 BMJ Publishing Group. All rights reserved.